Effect of organic fertilizer (pow humus) and potassium in the vegetative growth of tomato plant Lycopersicon esculentum Mill protected unheated conditions in sandy soil in Najaf al ashraf .Iraq.: Ali M.M.altalal Razzak k.R.aljebory - Aljebory, Razzak K.R.; Dawood, Abdulameer S.; Altalal, Ali M.M. (Journal of Kerbala for Agricultural Sciences, 2018)
An experiment was conducted on tomato plant (Dombito hybrid ) during the season of 2016/2017 in one of unheated plastic houses in the Technical Institute / Kufa in sandy soil, in the Governorate of Najaf al ashraf Iraq.This study included (16) interaction treatments this was agreement between four levels of granules of Humat potassium (pow humus) as a source of Humat (85%) is as a level of (0, 30, 60 and 90) g / m 2, and four levels of potassium are as levels of (0, 20, 40 and 60) kg / D used potassium nitrate (KNO3) (46.6%), as a metallic potassium fertilizer. Each of potassium nitrate and potassium Humat ware added at four intervals : - 1-The first payment addition was done to the soil (before (7) days) transplanting 2-The second was done with irrigation water, (15 days) after transplanting. 3- The third addition was done with irrigation water after bud opened . 4- The fourth addition was done after fruits setting. To study the effect the of vegetative growth of tomato plant in under plastic house conditions in sandy soil in the Governorate of Najaf .. Experiment was adopted according to the Split-Plot-Design with three replicates means were compared according to Duncan's Multiple Range test at the probability level of o.o5 . Results showed superiority of all treatment belong to (Humat potassium ((T, and all treatment of potassium addition A) in comparison, to control treatment in all vegetative growth and also interaction of ( T) x (A) significantly affected the above parameters compared to control treatment for the four picking (3, 6 , 9 , 12 ) The highest value for vegetative traits (plant height / cm, number of leaves / plant, leaf area / cm 2, leaf dry weight / g)ware obtained from (t4a4) (add 90 g / m 2 Humat potassium interacted with 60 kg / D / potassium)) The addition of it was respectively to recipes as aforesaid (236.5 cm), (59.25) and leaves / plants, (2988) cm 2, (9.19) g / plant, while , the 9th and 12th picking showed significant superiority in the most vegetative parameters , as achieved the highest values ​​compared to the 3rd and 6th pickings .